2023
DOI: 10.3390/biomedicines11051296
|View full text |Cite
|
Sign up to set email alerts
|

Initial Myeloid Cell Status Is Associated with Clinical Outcomes of Renal Cell Carcinoma

Abstract: The therapeutic outcome of immune checkpoint inhibition (ICI) can be improved through combination treatments with ICI therapy. Myeloid-derived suppressor cells (MDSCs) strongly suppress tumor immunity. MDSCs are a heterogeneous cell population, originating from the unusual differentiation of neutrophils/monocytes induced by environmental factors such as inflammation. The myeloid cell population consists of an indistinguishable mixture of various types of MDSCs and activated neutrophils/monocytes. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Next, Kawashita et al revealed that the degree of radiation-induced mucositis can be predicted on the basis of patient lymphocyte counts at the pre-radiation stage [5]. Other studies focusing on individual cancer types are included in this Special Edition, with research on breast cancer [6], renal cell carcinoma [7,8], ovarian cancer from ovarian endometrioma [9], and inflammatory bowel disease (IBD), conditions which sometimes transform into cancer-prone phenotype [10]. Breast cancer is the most commonly diagnosed cancer in women, and Uchida et al identified the nine candidate genes constituting therapeutic targets of breast cancer using existing databases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Next, Kawashita et al revealed that the degree of radiation-induced mucositis can be predicted on the basis of patient lymphocyte counts at the pre-radiation stage [5]. Other studies focusing on individual cancer types are included in this Special Edition, with research on breast cancer [6], renal cell carcinoma [7,8], ovarian cancer from ovarian endometrioma [9], and inflammatory bowel disease (IBD), conditions which sometimes transform into cancer-prone phenotype [10]. Breast cancer is the most commonly diagnosed cancer in women, and Uchida et al identified the nine candidate genes constituting therapeutic targets of breast cancer using existing databases.…”
mentioning
confidence: 99%
“…Clear cell renal cell carcinoma (ccRCC) is dominant in kidney cancer, the mortality rate for which has recently increased worldwide. Sabrina et al demonstrated that the outcome is predictable by the status of the myeloid cells during immune checkpoint inhibition (ICI) therapy [7]. Kurota et al showed the implication of the expression of the hemoglobin beta-chain in the tissue [8].…”
mentioning
confidence: 99%